An improved pig reference genome sequence to enable pig genetics and genomics research. Issue 6 (16th June 2020) - Warr, Amanda; Affara, Nabeel; Aken, Bronwen; Beiki, Hamid; Bickhart, Derek M; Billis, Konstantinos; Chow, William; Eory, Lel; Finlayson, Heather A; Flicek, Paul; Girón, Carlos G; Griffin, Darren K; et al.
Abstract: Background: The domestic pig ( Sus scrofa ) is important both as a food source and as a biomedical model given its similarity in size, anatomy, physiology, metabolism, pathology, and pharmacology to humans. The draft reference genome (Sscrofa10.2) of a purebred Duroc female pig established using older clone-based sequencing methods was incomplete, and unresolved redundancies, short-range order and orientation errors, and associated misassembled genes limited its utility. Results: We present 2 annotated highly contiguous chromosome-level genome assemblies created with more recent long-read technologies and a whole-genome shotgun strategy, 1 for the same Duroc female (Sscrofa11.1) and 1 for an outbred, composite-breed male (USMARCv1.0). Both assemblies are of substantially higher (>90-fold) continuity and accuracy than Sscrofa10.2. Conclusions: These highly contiguous assemblies plus annotation of a further 11 short-read assemblies provide an unprecedented view of the genetic make-up of this important agricultural and biomedical model species. We propose that the improved Duroc assembly (Sscrofa11.1) become the reference genome for genomic research in pigs.